Upaya Menciptakan Lingkungan Keluarga Bebas Depresi Dalam Mencegah Perilaku Bunuh Diri Remaja: Upaya Menciptakan Lingkungan Keluarga Bebas Depresi Dalam Mencegah Perilaku Bunuh Diri Remaja - Defi Astriani (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
Depression in adolescents is one of the increasing mental health problems in various parts of the world, including Indonesia. One of the extreme forms of depression that can occur is suicidal behavior. The family environment plays an important role in preventing suicidal behavior in adolescents, because the family is the first place to provide emotional and social support for the psychological development of adolescents. Therefore, efforts to create a family environment free from depression are very important in preventing suicidal behavior in adolescents. This study aims to explore various efforts that can be made by families to create an environment that supports adolescent mental health. This research is a qualitative – exploratory research. Participants in the research These are teenagers aged 12-18 years who tend to be depressed and have suicidal thoughts. and families living in the same house. The results of the study showed that family efforts in creating a depression-free family environment include open and empathetic communication, increasing awareness of mental health, providing stable emotional support, and strengthening emotional bonds between parents and children. In addition, education about the signs of depression in adolescents and the importance of seeking professional help are important aspects in suicide prevention. By creating a caring, responsive, and loving family, it is hoped that a safer atmosphere can be created for adolescents to express their feelings, thereby reducing the risk of suicidal behavior that can be caused by untreated depression.